Characterization, performance and optimization of nanolubricants in automotive air-conditioning with electrically-driven compressor - Mohd Hamisa, Abdul Hamid (2023)
The automotive air-conditioning (AAC) system consumes the most energy among the auxiliary components in vehicles to achieve thermal comfort inside the vehicle's cabin. Nanolubricant was used to improve the performance of the AAC system. Few studies investigated the AAC system performance with nanolubricant but were mainly concerned with belting-driven compressor (BDC) and polyalkylene-glycol (PAG) nanolubricant. However, a limited study was undertaken for AAC with an electrically-driven compressor (AAC-EDC) with polyolester (POE) lubricant and none with nanolubricant. Therefore, using nanolubricant in AAC-EDC system is expected to increase the performance and minimize the size of the battery and AAC components. This study aims to evaluate the rheological and tribological properties of the POE nanolubricants and evaluate the performance and optimize the operating parameters of the AAC-EDC system. The POE nanolubricant was formulated and stabilized using a two-step method of preparation. Mono TiO2/POE, mono SiO2/POE and hybrid TiO2-SiO2/POE nanolubricants were prepared at different volume concentrations of 0.01 to 0.1%. Quantitative and qualitative methods were used to assess the stability of nanolubricants. The rheological properties were measured at a temperature of 30 to 100 °C. Meanwhile, the four-ball tester was used to evaluate the tribological properties of nanolubricants according to ASTM D4172-18 standard. Further, the AAC-EDC experiment was performed in the range of 1200 to 3840 rpm compressor speed and 120 to 160 g for the initial refrigerant charge. Response surface methodology (RSM) and analysis of variance (ANOVA) were used in the optimization to investigate the influence of compressor speed, initial refrigerant charge, and volume concentration as input parameters on the AAC-EDC performance with nanolubricants. All nanolubricants were found to have excellent stability, with minor sedimentation for up to 30 days of observation. The visual observation results were supported by ultra-violet visible (UV-Vis) spectroscopy evaluation. The mono and hybrid nanolubricants were sustained for over 90% of the UV-Vis concentration ratio for up to 30 days. The zeta potential at more than 60 mV for all nanolubricants further confirmed the excellent stability condition. The dynamic viscosity of the mono and hybrid nanolubricants was increased with volume concentration while decreasing with temperature. Interestingly, the dynamic viscosity decrement occurred for nanolubricants at less than 0.05% volume concentration compared to pure POE lubricant. The tribological evaluation was performed with a better coefficient of friction (COF) and wear scar diameter (WSD) compared to pure POE lubricant at less than 0.05% volume concentrations for all nanolubricants. The mono SiO2/POE nanolubricant in the AAC-EDC system performed better than pure POE lubricant, mono TiO2/POE and hybrid TiO2-SiO2/POE nanolubricant with a reduction in compressor work of 22.3%, heat absorption increment up to 110% and COP enhancement up to 53.8% at 0.01% volume concentration. From RSM optimization, the optimum parameter, namely compressor speed, initial refrigerant charge and volume concentrations of 1808 rpm, 160 g and 0.013%, respectively, yield the optimum responses of heat absorption, compressor work, expansion valve discharge temperature, and EDC power consumption for SiO2/POE nanolubricant were attained at 19.91 kJ/kg, 5.34 kJ/kg, 10.28 °C and 116.66 W respectively with highest desirability of 0.941. It can be concluded that a 0.013% volume concentration of SiO2/POE nanolubricant was highly recommended for optimum performance in the AAC-EDC system. Therefore, it is recommended to employ these nanolubricants in the actual vehicle conditions and can also be applied in better environment refrigerants such as R1234yf.